The implementation of population education in the division of Biliran - Engle, Tarcela de la Cruz (Tacloban City, Philippines DWU Graduate School Publication, 1981)
"This is a descriptive statistical survey which attempts to obtain a general picture of the implementation of the Population Education Program in the Division of Biliran during the school year 1979-1980. A questionnaire is the principal instrument used in data gathering, copies of which were distributed to 209 public elementary school teachers in the eight central schools in the Division of Biliran. The study yields three kinds of data: nominal, ordinal and interval data. Data on teachers' attitudes are interval data which necessitates statistical tools like critical ration and analysis of variance. Findings of the study reveals the majority of the Population Education teachers do not have adequate preparation to teach the subject since they have not taken Population Education courses and in-service training on Population Education. "
Keywords: Dissertations -- Leyte; Education -- Population